The satisfaction of residents of residential homes in Jordan over atrium daylight - Marzuki, Ibrahim; Haytham, Jaradat (2021)
This research was conducted to measure the level of satisfaction of residential occupants who use atrial roof architecture with daylight in terms of interior design suitability, thermal comfort, and internal visual comfort. The quantitative research method using this survey question involved 355 residential residents in Amman, Jordan. Respondents consisted of 40.3% women and 59.7% men aged 25 to 50 years and above. Findings from this research show that ridge roofs recorded the highest percentage overall as compared to other types of roofs listed in this study (68.2%). The collected data were coded, and SPSS version 23 was used to analyze all the data. The conclusions from this study indicate that Jordanians are satisfied with daylight on their atrium roof in terms of interior design suitability, thermal comfort, and interior visual comfort. Findings from the study suggest that daylight illumination in the atrium in Jordanian residential buildings is essential to analyze and it is also very closely related to the factors that have been identified; interior design, thermal comfort as well as visual comfort. All these factors have helped in giving exposure to the housing contractors involved in the aspects that need to be given special attention when doing the design work and manufacture of a product.